163 Actigraphy-measured circadian factors and mortality in US adults: Results from the NHANES. (3rd May 2021) - Lin, Zhuozhi; Rojo-Wissar, Darlynn; Nestadt, Paul; Urbanek, Jacek; Di, Junrui; Zipunnikov, Vadim; Spira, Adam
Abstract: Introduction: Chronotype is a potentially modifiable contributor to human well-being and longevity, with eveningness commonly linked to poorer outcomes. We examined the relationship between actigraphy-measured chronotype and all-cause mortality in a nationally representative sample of US adults. We also examined the association between social jetlag, a measure of circadian misalignment, and all-cause mortality. Methods: Data were from 2, 256 participants ≥50 from the National Health and Nutrition Examination Survey 2003-2006 cohorts. Participants were asked to wear a hip-worn Actigraph 7164 uni-axial activity monitor for 7 days, and to remove the device for sleep. Objectively-measured bedtime (OBT) was computed as the start of the non-wear period with the longest duration within each 24h period. Duration of the in-bed period (OBT-D) was computed as the hours from OBT to the end of the in-bed period. Midpoint of OBT (OBT-M) was computed as the midpoint between OBT and the end of the in-bed period. Chronotype was estimated using the average OBT-M separately for weekdays, weekends (Friday and Saturday nights), and all days combined. A weekend OBT-M corrected for sleep debt for participants with weekend OBT-D>weekday OBT-D was also computed. The following formula was applied to correct for sleep debt: weekend OBT-M minus ((weekend OBT-D minus weekday OBT-D)/2). Consistent with previous research, OBT-Ms were categorized into intermediate (≥3:30am & ≤4:30am), morningness (<3:30am), and eveningness (>4:30am) chronotypes. Social jetlag was defined as the difference between weekend and weekday OBT-Ms and expressed in hours. Survey-weighted Cox proportional hazard models were used to examine the relationship between circadian factors and all-cause mortality. There were 642 deaths, excluding accidental deaths. Results: Adjusted for age, sex, race, SES, BMI, smoking and drinking status, comorbidities, and average OBT-D, an eveningness chronotype (i.e., weekend OBT-M corrected for sleep debt) was associated with a greater hazard of death compared to an intermediate chronotype (HR=1.68, 95% CI=1.25, 2.26). There were no other significant associations. Conclusion: Evening-oriented chronotype is associated with greater mortality risk in adults aged ≥50. To our knowledge, this is the first study to report the link between chronotype, estimated objectively via actigraphy, and all-cause mortality in a nationally representative sample. Support (if any): NIH grant 5T32MH014592-39.